2022
DOI: 10.3389/fonc.2022.1032746
|View full text |Cite
|
Sign up to set email alerts
|

Progression of hepatocellular carcinoma after radiofrequency ablation: Current status of research

Abstract: Hepatocellular carcinoma (HCC) remains an important disease for health care systems in view of its high morbidity, mortality, and increasing incidence worldwide. Radiofrequency ablation (RFA) is preferred to surgery as a local treatment for HCC because it is safer, less traumatic, less painful, better tolerated, causes fewer adverse reactions, and allows more rapid postoperative recovery. The biggest shortcoming of RFA when used to treat HCC is the high incidence of residual tumor, which is often attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Future studies should explore whether total ablation further improves abscopal response in immune "cold" as well as immune "hot" tumor models. Notably, literature has shown that thermal ablation methods, such as radiofrequency (RF) ablation, induce counterproductive responses in partial ablation experimental mouse models, where partial ablation induced stronger primary tumor growth and greater metastatic potential of the treated tumor [29][30][31] suggesting a significant risk when patients receive incomplete or discontinuous RF ablation. Comparably, partial PEF ablation was not observed to incur these effects here, consistent with [24], which demonstrated PEF partial ablation invoked superior immunostimulation, tumor response, and mouse survival relative to RF ablation.…”
Section: Plos Onementioning
confidence: 99%
“…Future studies should explore whether total ablation further improves abscopal response in immune "cold" as well as immune "hot" tumor models. Notably, literature has shown that thermal ablation methods, such as radiofrequency (RF) ablation, induce counterproductive responses in partial ablation experimental mouse models, where partial ablation induced stronger primary tumor growth and greater metastatic potential of the treated tumor [29][30][31] suggesting a significant risk when patients receive incomplete or discontinuous RF ablation. Comparably, partial PEF ablation was not observed to incur these effects here, consistent with [24], which demonstrated PEF partial ablation invoked superior immunostimulation, tumor response, and mouse survival relative to RF ablation.…”
Section: Plos Onementioning
confidence: 99%
“… 4 Because of decompensated liver function, portal hypertension, and organ shortage, surgical resection, and liver transplantation are limited in many cases. 5 , 6 As a minimally invasive treatment, ablation has a similar prognosis to surgical resection and exhibits the advantages of fewer complications. 7 , 8 However, the prognosis of ablation remains unsatisfactory, with a 5-year recurrence rate of 50–70%, which leads to shorter survival of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…During the procedure of percutaneous thermal ablation for HCC, ultrasound is the conventionally preferred real-time imaging modality to guide the needling position, track tumor lesions during hepatic, respiratory movement, and avoid the injury of vital organs (5). Moreover, optimized ultrasound guidance is necessary to confirm the immediate efficacy of the treatment and reduce the incidence of local tumor progression (LTP) during follow-up (6,7). However, not all HCC lesions were with adequate visibility on conventional ultrasound, such as those with small size (diameter <2 cm), with the isoechoic feature, or in difficult locations within the body (8,9).…”
Section: Introductionmentioning
confidence: 99%